Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3892/etm.2021.11105
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A attenuates oxidative stress injury‑induced apoptosis in the nucleus pulposus cell line and regulates extracellular matrix balance via CA XII

Abstract: Intervertebral disc degeneration (IVDD) is the main cause of lower back pain. Oxidative stress injury and degradation of the extracellular matrix (ECM) are important factors causing IVDD, while hydroxysafflor yellow A (HSYA) has significant anti-oxidative stress and anti-apoptotic effects. The present study aimed to investigate the protective role of HSYA in IVDD using nucleus pulposus (NP) cells. A Cell Counting Kit-8 assay was used to detect cell viability following HSYA and tert-Butyl hydroperoxide (TBHP) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…It has been reported that HSYA can significantly reverse the apoptosis of endplate chondrocytes during the progression of IDD [ 11 ]. In the current study, HSYA was able to protect endplate chondrocytes against IL-1 β -induced injury through promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that HSYA can significantly reverse the apoptosis of endplate chondrocytes during the progression of IDD [ 11 ]. In the current study, HSYA was able to protect endplate chondrocytes against IL-1 β -induced injury through promoting autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxysafflor yellow A (HSYA), a component of safflower, which was reported to exhibit neuroprotective, antioxidant, anti-inflammatory and other pharmacological activities in many diseases [ 10 ]. In addition, Yang, Liao reported that HSYA might serve as a potential agent to treat IDD [ 11 ]. For example, HSYA could significantly inhibit the apoptosis of endplate chondrocytes during the progression of IDD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imbalance between ECM synthesis and degradation is the main pathological feature of IDD (Sakai et al, 2012). Matrix metalloproteinase (MMPs) and ADAMTS are the main catabolic enzymes in IVD with high content in degenerated IVDs (Le Maitre et al, 2007), and they accelerate the degradation of ECM (Le Maitre et al, 2007; Weiler et al, 2002; Yang & Liao, 2021). Meanwhile, the calcification of CEP leads to a decrease in its permeability, hindering the exchange of nutrients in the center of the IVDs (Feng et al, 2016).…”
Section: Overview Of Intervertebral Disc Degenerationmentioning
confidence: 99%
“…Thus, therapeutic targets for maintaining ECM equilibrium may be crucial for preventing disc degeneration. For example, hydroxysafflor yellow A inhibits TBHP-induced oxidative stress in an NP cell line and modulates ECM equilibrium through carbonic anhydrase 12 (CA XII) [ 334 ]. Under oxidative stress, resveratrol promotes ECM production in NP cells by activating autophagy via the PI3K/Akt pathway [ 335 ].…”
Section: Autophagy As a Potential Therapeutic Target For Ivddmentioning
confidence: 99%